2017
DOI: 10.15326/jcopdf.4.2.2016.0159
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Chronic Obstructive Pulmonary Disease Overlap: The Effect of Definitions on Measures of Burden

Abstract: Background: Although the overlap between asthma and COPD has been recognized for years this overlap has only recently been given a name, asthma-COPD overlap syndrome (ACOS), and better defined. Different definitions of the component diseases can affect prevalence and outcome measures of ACOS. Methods: We used data from the National Health and Nutrition Examination Survey (NHANES) from [2007][2008][2009][2010][2011][2012] to determine the population estimates of ACOS in U.S. adults using 2 different definitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…The study characteristics of the included studies are summarized in Table 2. In total, we included 27 studies published since 2011, except for one study that published in 1996: twelve from Europe [10, 12, 13, 16, 17, 20, 23, 25, 2830, 35], nine from the North America (United States and Canada) [11, 15, 18, 21, 26, 27, 3234], three East Asia (China and Korea) [19, 22, 36], three from the Latin America and 6 low- and middle-income countries and Australia [14, 24, 31]. The majority of the included studies were published after 2015.…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics of the included studies are summarized in Table 2. In total, we included 27 studies published since 2011, except for one study that published in 1996: twelve from Europe [10, 12, 13, 16, 17, 20, 23, 25, 2830, 35], nine from the North America (United States and Canada) [11, 15, 18, 21, 26, 27, 3234], three East Asia (China and Korea) [19, 22, 36], three from the Latin America and 6 low- and middle-income countries and Australia [14, 24, 31]. The majority of the included studies were published after 2015.…”
Section: Resultsmentioning
confidence: 99%
“…According to international guidelines, COPD is diagnosed only when airflow obstruction is documented by spirometry (11, 12, 13). The only U.S. study that used spirometry defined COPD as Forced Expiratory Volume in 1 second (FEV1) / Forced Vital Capacity (FVC) < 70% pre-bronchodilator administration, instead of the post-bronchodilator as suggested by the GOLD (14). Furthermore, ACO features are yet to be fully described and there is a need to identify biomarkers that differentiate ACO from asthma and COPD (15).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study incorporated elements of this approach by tracking features such as persistent airflow limitation, 40 years of age or older, a history of asthma during early life, and significant smoke exposure (⩾10 pack-years) [40]. Importantly, there remains no global consensus on appropriate diagnostic criteria for ACO, and the implementation of different criteria among epidemiologic studies has produced significant variations in reported statistics for disease prevalence and outcomes [12,42,43]. These limitations are intrinsic to the conventional systems of disease labelling, which may be addressed by incorporating elements of the treatable traits strategy to characterise the complexity and heterogeneity of ACO.…”
Section: Current Definitions and Diagnostic Criteriamentioning
confidence: 99%